Odpowiedzi

Najlepsza Odpowiedź!
2010-01-05T21:01:04+01:00
A) 4x ( x-2 ) = ( 2x + 4)* oznaczenia
4x* - 8x = 4x* + 16x + 16 *- do kwadratu
4x* - 8x - 4x - 16x = 16
-8x - 16x = 16
-24x = 16 /: (-24)
x= 0,6(6)

B) x (2x -1) = 2 (x + 2 )*
2x* - x = 2 (x* +4x + 4)
2x* -x = 2x* +8x + 8
2x* - x - 2x* -8x = 8
-9x = 8 /: (-9)
x= 0,8(8)

C) 2x - x* = 1 - (x + 3 )*
2x - x* =1-( x* +6x +9)
2x - x*= 1-x*-6x-9
2x-x*+x*+6x=-8
8x=-8/: 8
x=-1

D) (x+1)* + (x-2)*= 2 (x-1)(x+)
x*+2x+1+x*-4x+4=2(x-2)*
x*+2x+1+x*-4x+4=2(x*-2x+1)
2x*-2x+5=2x*-4x+2
2x*-2x* -2x +4x=2-5
2x=-3/:2
x= -1,5

powinno być dobrze;)